ImmGen at 15 - Aguilar, SV; Aguilar, O; Allan, R; Blair, D; Dustin, ML; Immunological Genome Project; Et al. (Nature Research, 2020)
The Immunological Genome Project (ImmGen) is a collaborative group of immunology and computational biology laboratories that perform a thorough dissection of gene expression and its regulation in the immune system of the mouse. This activity first centered on mRNA expression and then expanded to microRNA (miRNA), chromatin structure, nuclear organization and protein–RNA relationships. Shared protocols, data generation and QC pipelines have yielded data that can be directly compared from >250 stem, lymphoid and myeloid cell types, at baseline or under challenge. The group develops and applies computational tools to decipher regulatory connections and transcriptional control. From its inception, data generated by ImmGen were meant to be a public resource, and they can be accessed through dedicated web and smartphone platforms that use interactive graphic displays that make the results intuitive to users.